Sistem Informasi Monitoring SPJ Fungsional Sekretariat Daerah Kabupaten Kolaka - Novi Cahya Lestari; Alhilal Anwar; Intan Anuggrah Yuandi (Perhimpunan Ahli Teknologi Informasi dan Komunikasi Indonesia, 2024)
The management of Accountability Reports (SPJ) is a critical aspect of budget management in government institutions. The Department of Economy and Natural Resources (BPSDA) at the Regional Secretariat of Kolaka Regency has been using an Excel-based system for SPJ management, leading to difficulties in accessibility, accuracy, and real-time budget monitoring. This research aims to develop a Web-Based Functional SPJ Monitoring Information System to facilitate more effective and efficient SPJ management. The system was developed using the Laravel framework and MySQL database, following the Waterfall development method. The results show that the system can assist users such as the Assistant Treasurer (BPP), Technical Activity Executing Officer (PPTK), and Head of Division (Kabag) in monitoring SPJ functionality in real-time. The system was tested using the Blackbox method, and the results indicate that it operates according to the designed specifications. This system enhances transparency, accuracy, and ease of access in SPJ management at BPSDA of Kolaka Regency, thus improving budget management efficiency